Multifunctional bioactive coatings based on water-soluble chitosan with pomegranate peel extract for fish flesh preservation. (16th April 2022) - Yu, Dawei; Zhao, Wenyu; Dong, Junli; Zang, Jinhong; Regenstein, Joe M.; Jiang, Qixing; Xia, Wenshui
Highlights: CMCS coating combined with PPE retarded the quality loss of grass carp fillets. Multifunctional coating retarded texture softening and juice loss of fillets. The coating inhibited the bacterial growth especially Shewanella . The carp fillets with CMCS-PPE coating had the refrigerated shelf life of ≥9 days. Similar performance of the coating was verified in longsnout catfish and snakehead. Abstract: This study aimed to reveal the effects of vacuum-impregnated carboxymethyl chitosan (CMCS) coating with pomegranate peel extract (PPE) on quality retention of fish flesh during refrigeration. Herein, CMCS-PPE coating was effective in attenuating quality loss of grass carp fillets. Compared to Control, the levels of drip loss, total volatile base nitrogen, and K value in coated samples were sharply decreased ( p  < 0.05) by 24.5%, 35.3% and 25.2% on day 9, respectively. Meanwhile, the coating also helped inhibit oxidation, bioamine accumulation, and texture softening in fillets. Moreover, the microbial enumeration was reduced by >1.4 lg cfu/g as compared to Control on day 6 afterward, and high throughput sequencing analysis further showed the active coating contributed to the notable growth suppression of spoilage bacteria like Shewanella . Additionally, the positive effect of the coating scheme was also verified in longsnout catfish and snakehead, further confirming its good applicability for fish flesh preservation.